California, in-doors and out; or, How we farm, mine, and live generally in the Golden State. - Farnham, Eliza W. (Eliza Wood), 1815-1864. (New York, Dix, Edwards, 1856)
During her three years as matron of the Female Prison at Sing Sing, 1844-1848, Eliza Burhans Farnham (1815-1864) tried to institute reforms based on phrenology. Discharged from the post, she soon learned that her lawyer-husband had died in California, leaving her with affairs to settle there. Farnham set about organizing a pioneer party of single, educated women to join her in the voyage round the Horn. California, in-doors and out (1856) opens with a description of her harrowing voyage round the Horn in 1849. In 1850 Farnham and her children moved to El Rancho La Libertad, the Santa Cruz farm left to her by her husband. She describes her experiences as a farmer, the position of women in California, mining life, the history of the Donner Expedition based on interviews with survivors, and the 1856 San Francisco Vigilance Committee.
"The Donner emigration of 1846": p. 380-457.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Description and travel; California -- Gold discoveries; Donner Party; Women -- California; Urbanization -- California; Law -- Political aspects -- California; Mines and mineral resources -- California; Agriculture -- California